Efficacy of CAD/CAM Glass Fiber Posts for the Restoration of Endodontically Treated Teeth - Maira Alejandra Gutiérrez; Camilo Alejandro Guerrero; Paula Alejandra Baldion (International Journal of Biomaterials)
Objective. The aim of this systematic review was to provide an overview of available scientific evidence regarding the comparative efficacy of computer-aided design (CAD) and computer-aided manufacturing (CAM) glass fiber posts with prefabricated and metal cast posts for the restoration of endodontically treated teeth (ETT). Methods. This systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Electronic and manual searches were performed using the PubMed, SciELO, Cochrane, ScienceDirect, Web of Science, and EBSCO databases. The reference lists of the selected papers were reviewed to identify relevant papers. There were no year restrictions, and eligible studies were those in English publications and describing in vitro studies evaluating intraradicular retainers (IRs) for (i) fracture resistance, (ii) bond strength, (iii) adaptation, and (iv) cement layer thickness. Literature reviews, systematic reviews, meta-analyses, case reports, in vitro studies with <8 specimens, and noncomparative trials involving prefabricated or metal cast posts were excluded. The authors of this review independently screened the search results, extracted data, and assessed the risk of bias. Results. No significant differences were found in fracture resistance between prefabricated and CAD/CAM glass fiber posts or between CAD/CAM glass fiber and metal cast posts, although the latter demonstrated higher fracture resistance than the prefabricated glass fiber posts. Restoration with a full crown was not necessary to increase the fracture resistance in the presence of the ferrule effect. CAD/CAM glass fiber and metal cast posts had higher bond strength, lower nanoleakage, and better adaptation to the root canal. Conclusions. Despite the heterogeneity of methodologies and results reported, the results of these studies indicated that the CAD/CAM glass fiber and metal cast posts showed greater efficacy in terms of fracture resistance, retention, and adaptation, compared to prefabricated glass fiber posts.